Interaction and Foreign Language Learning: A Theoretical Framework - Rabia Börekçi; Selami Aydin (Literacy Trek, 2018)
While interaction has a considerable role in the foreign language learning and teaching processes, how it relates to the current theories is still an unanswered question. Thus, this paper aims to present a theoretical framework that focuses on interaction and the foreign language learning and teaching processes. For this purpose, the paper first introduces the term interaction and clarifies its importance in human life, the relationship between interaction and learning. Then, the paper focuses on the factors affecting interaction in the learning process, the importance of interaction in foreign language learning and related theories and hypotheses. The paper concludes that interaction in the foreign language learning and teaching processes enhances personal development, motivation, participation and linguistic knowledge.